Pengembangan Bio-Meta: Buku Digital Terintegrasi Dengan Augmented Reality dan Virtual Reality - Mahrawi Mahrawi; Pipit Marianingsih; Annisa Artdhita Nirmala Putri Saputro; Putri Intan Pardede; Ardia Regita Cahyani; Rizka Chaerunisa (Peneliti.net, 2023)
This study aims to Develop Bio-Meta which integrates digital books with augmented reality and virtual reality in visualizing the concept of plant growth and Development, to Develop Bio-Meta as an interactive digital learning medium that can improve students' digital literacy, and to determine the feasibility of using it. Bio-Meta: Integrated Digital book With Augmented reality And Virtual reality from experts and samples. This research is a Development research (R&D). This research was conducted from January to September 2022 at Sultan Ageng Tirtayasa University and SMAN 2 Serang City. The research sample consisted of 20 students of class XII science. The process of Developing learning media is carried out with the stages of Analyze, Design, Develop, Implement and Evaluate (ADDIE). The applications used are Canva, Sketchfab.com, 3DVista, WebAR Zappar, and Heyzine Flipbooks. The results of the expert test analysis showed that the average score of the media expert team was 88.3% and the material expert team was 84.2% with the very good media category. The results of the student response test show that the media feasibility interpretation score from the use of the SUS instrument is 81.3 so that it meets the criteria for an interpretation score of more than 80.3 which means that Bio-Meta is a good media and students accept the Bio-Meta learning media as a suitable media to use. to help students understand the nervous system material.